Representation as Collective Memory: Carnivalesque and Orality in Eldorado West One by Sam Selvon - Pisano, Carlotta (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2022)
In Sam Selvon’s seven one-act radio-drama Eldorado West One, written for BBC radio in 1969, a universe of colours, contrasts, accents, nostalgia, and struggle that peculiarise the life experience of the Caribbean community in London is at stake. The main characters of the play are the same as in the well-known novel The Lonely Londoners (1956), re-represented in a theatrical context, constructed on the orality and urban communication, reinvented through the immediate representation of radio actors and the expression of the Trinidadian Creole Language. The surrounding reality described by Selvon's conscious disillusionment is interwoven with the historical events that have marked British society, such as the massive migration from the Caribbean territories to London, like the Windrush generation in the 50s, that, in the last decades, have shaped the United Kingdom into a cross-cultural society. This essay is an attempt to show, from a linguistic reflection to ethnographic data about Trinidadian Carnival, how we incur in these elements through the play indicated above; through the connection in Selvon’s narrative between the Caribbean heritage, in particular the manifestation of the subculture related to the Trinidadian Carnival, the Creole and Calypso music; and the syncretism created by the tradition and the contact with the Western culture, in the era of European decolonisation during the 20th century.